The Complex GNAS Imprinted Locus and Mesenchymal Stem Cells Differentiation - Elli, F. M.; Boldrin, V.; Pirelli, A.; Spada, A.; Mantovani, G. (Hormone and Metabolic Research, 2016)
All tissues and organs derive from stem cells, which are undifferentiated cells able to differentiate into specialized cells and self-renewal. In mammals, there are embryonic stem cells that generate germ layers, and adult stem cells, which act as a repair system for the body and maintain the normal turnover of regenerative organs. Mesenchymal stem cells (MSCs) are nonhematopoietic adult multipotent cells, which reside in virtually all postnatal organs and tissues, and, under appropriate in vitro conditions, are capable to differentiate into osteogenic, adipogenic, chondrogenic, myogenic, and neurogenic lineages. Their commitment and differentiation depend on several interacting signaling pathways and transcription factors. Most GNAS-based disorders have the common feature of episodic de novo formation of islands of extraskeletal, qualitatively normal, bone in skin and subcutaneous fat. The tissue distribution of these lesions suggests that pathogenesis involves abnormal differentiation of MSCs and/or more committed precursor cells that are present in subcutaneous tissues. Data coming from transgenic mice support the concept that GNAS is a key factor in the regulation of lineage switching between osteoblast and adipocyte fates, and that its role may be to prevent bone formation in tissues where bone should not form. Despite the growing knowledge about the process of heterotopic ossification in rare genetic disorders, the pathophysiological mechanisms by which alterations of cAMP signaling lead to ectopic bone formation in the context of mesenchymal tissues is not fully understood.
Keywords: GNAS; mesenchyamal stem cells; imprinting; ectopic bone formation; osteoblast; adipocyte